PERAN PERGURUAN TINGGI DALAM PENCEGAHAN KEKERASAN DALAM RUMAH TANGGA (KDRT) DI MASA PANDEMI - Sa'diyah, Nur Khalimatus; Enggarsasi, Umi; Prameswari, Septiana (Lembaga Penelitian dan Pengabdian Masyarakat, 2023)
Based on data released by the Ministry of Women's Empowerment and Child Protection of the Republic of Indonesia (Kemenpppa), the number of cases of Domestic Violence (KDRT) that occurred in Indonesia throughout 2020 was still very high. East Java ranks second highest after Central Java as the province with the most domestic violence cases throughout 2020, with 1,588 cases. This figure is obtained from the number of cases of domestic violence reported in all cities in East Java. Efforts to reduce the incidence of domestic violence are not enough just to take repressive actions against perpetrators of domestic violence. What is more important is preventive action to prevent the occurrence of domestic violence. One of the causes of domestic violence can occur is the lack of public knowledge about what is meant by domestic violence. Because there are still many cases of domestic violence that occur during this Covid-19 Pandemic. This is where the role of universities is expected to be able to provide knowledge to the community, not only for women or children, but also for men. One of the things that universities can do in providing knowledge to the community regarding domestic violence is by conducting socialization and legal counseling. The role of legal counseling can provide increased legal knowledge to community members in order to avoid violations of the law, especially Law Number 23 of 2004 concerning the Elimination of Domestic Violence. Another benefit of legal counseling is that the community can play an active role directly with other communities to transmit or relay the relay to other members of the community such as within the family, neighbors, in the neighborhood associations and neighborhood associations in the East Java region. Keywords: College, Domestic Violence, Pandemic